The Legality of Picketing - Handman, Suzanne; Leopold, John (Relations industrielles / Industrial Relations, 1979)
The authors attempt, by means of « jurisprudence » to determine the conditions and circumstances which render picketing legal or illegal. Within this context, picketing will be examined from the point of view of object, form and occasion. In addition, the sanction of picketing will be presented, followed by a critique of the subject.